The pity of war - Ferguson, Niall (New York, N.Y. Basic Books, 1999)
"In The Pity of War, Niall Ferguson explodes the myths of 1914-18. He argues that the fatal conflict between Britain and Germany was far from inevitable. It was Britain's declaration of war that needlessly turned a continental conflict into a world war, and it was Britain's economic mismanagement and military inferiority that necessitated American involvement, forever altering the global balance of power." "Ferguson vividly brings back to life one of the seminal catastrophes of the century, not through a dry citation of chronological chapter and verse, but through a series of chapters that answer the key questions: Why did the war start? Why did it continue? And why did it stop? How did the Germans manage to kill more soldiers than they lost but still end up defeated in November 1918? Above all, why did men fight?"--Jacket.
ch. 1. Myths of militarism -- ch. 2. Empires, ententes and Edwardian appeasement -- ch. 3. Britain's war of illusions -- ch. 4. Arms and men -- ch. 5. Public finance and national security -- ch. 6. Last days of mankind: 28 June - 4 August 1914 -- ch. 7. August days: the myth of war enthusiasm -- ch. 8. Press gang -- ch. 9. Economic capability: the advantage squandered -- ch. 10. Strategy, tactics and the net body count -- ch. 11. 'Maximum slaughter at minimum expense': war finance -- ch. 12. Death instinct: why men fought -- ch. 13. Captor's dilemma -- ch. 14. How (not) to pay for the war.
CSSP-6576 donated by The Rotary Club Beaverton, Oregon, United States of America.
Keywords: World War, 1914-1918.; Great Britain -- History -- 20th century